If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x(8x + -7) + -8x(9x + -8) = 0 Reorder the terms: 8x(-7 + 8x) + -8x(9x + -8) = 0 (-7 * 8x + 8x * 8x) + -8x(9x + -8) = 0 (-56x + 64x2) + -8x(9x + -8) = 0 Reorder the terms: -56x + 64x2 + -8x(-8 + 9x) = 0 -56x + 64x2 + (-8 * -8x + 9x * -8x) = 0 -56x + 64x2 + (64x + -72x2) = 0 Reorder the terms: -56x + 64x + 64x2 + -72x2 = 0 Combine like terms: -56x + 64x = 8x 8x + 64x2 + -72x2 = 0 Combine like terms: 64x2 + -72x2 = -8x2 8x + -8x2 = 0 Solving 8x + -8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '8x'. 8x(1 + -1x) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {0, 1}
| 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 | | x*x^3*x^3= | | (b^2+3b-9)/(b+5) | | 8/c+2-6=4/c+2 | | C(c+2)=12 | | W(w-5)=14 | | 6z-15=3z+12 | | t^2/2+2t=-1/4 | | 1/4(8-8x)=1/2(4x+2) | | 7+4(z-8)=3-3z | | 3x-6=2x+15 | | x-10x+25=0 | | (4v-6)(1+v)=0 | | 99.08/100*40.65=x | | 8n=6-14 | | 5x-2-7x=4+x-1 | | -2x-1/16=-6x^2 | | 56=4h/7 | | X^4-12x^4+48x^2-64=0 | | -7w=-91 | | -22=-p | | 8t-20=6t+10 | | 15n^2+19n+6=10+2n | | 3x^2+10x+15=-4X | | 15n^2+19+6=10+2n | | 0.02*40.65=x | | (x-2)=36 | | -64+30m=-34 |